Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1755-3768.2012.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins 6-12 in the human eye

Abstract: ABSTRACT.Purpose: Aquaporins (AQPs) are widely expressed and have diverse distribution patterns in the eye. AQPs 0-5 have been localized at the cellular level in human eyes. We investigated the presence of the more recently discovered AQPs 6-12 in the human eye. Methods: RT-PCR was performed on fresh tissue from two human eyes divided into the cornea, corneal limbus, ciliary body and iris, lens, choroid, optic nerve, retina and sclera. Each structure was examined to detect the mRNA of AQPs 6-12. Twenty-one hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
0
25
1
Order By: Relevance
“…Lens epithelial cells contain AQP1 [15]. Recent immunohistochemistry studies also demonstrated AQP5 and AQP7 labeling in the lens epithelium; however, their relative abundance has not been measured [6567]. In lens fiber cells, AQP0, formerly known as major intrinsic protein (MIP), is highly abundant comprising over 50% of lens membrane protein concentration.…”
Section: Lensmentioning
confidence: 99%
“…Lens epithelial cells contain AQP1 [15]. Recent immunohistochemistry studies also demonstrated AQP5 and AQP7 labeling in the lens epithelium; however, their relative abundance has not been measured [6567]. In lens fiber cells, AQP0, formerly known as major intrinsic protein (MIP), is highly abundant comprising over 50% of lens membrane protein concentration.…”
Section: Lensmentioning
confidence: 99%
“…In these original reports, AQP9 mRNA expression was found in a few tissues, most notably liver and leukocytes in humans (Ishibashi et al 1998;Tsukaguchi et al 1999), as well as liver and immature sperm in mice (Tsukaguchi et al 1998). Since then, AQP9 immunoreactivity has been found in many tissues, including rat and human epididymis (Elkjaer et al 2000;Pastor-Soler et al 2001), various cell types of rodent and primate brain (Elkjaer et al 2000;Badaut et al 2001;Badaut et al 2004;Amiry-Moghaddam et al 2005;Arcienega et al 2010), mouse spinal cord (Oshio et al 2004), human chorioamnion and placenta (Damiano et al 2001;Wang et al 2004), mouse and human inner ear (Huang et al 2002;Degerman et al 2011), mouse and human small intestine (Okada et al 2003), rat and human prostate (Wang et al 2008;Hwang et al 2012), human skeletal muscle (Inoue et al 2009), urothelium (Rubenwolf et al 2009), rat and porcine oviduct (Skowronski et al 2009), human adipose tissue (Rodriguez et al 2011), human retina (Tran et al 2013;Yang et al 2013), and mouse and human skin (Sugiyama et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…7 However, more recently, human native RPE cells have been shown to express several other AQPs, including AQP0, AQP1, AQP3, AQP4, AQP5, AQP6, AQP7, AQP8, AQP9, AQP10, AQP11, and AQP12, but not AQP2. 8,9 In addition, in a microarray study AQP3 was shown to be expressed by human stem cell-derived mature RPE cells but not by an immortalized RPE cell line. 10 In a similar microarray survey mature stem cellderived RPE cells were shown to also express AQP1.…”
mentioning
confidence: 99%